2020
DOI: 10.1186/s13031-020-00305-w
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking, trust and intimate partner violence: social connections amongst displaced and non-displaced Yezidi women and men in the Kurdistan region of northern Iraq

Abstract: Background: Conflict and displacement impact the social fabric of communities through the disruption of social connections and the erosion of trust. Effective humanitarian assistance requires understanding the social capital that shapes patterns of help-seeking in these circumstances-especially with stigmatised issues such as violence against women (VAW) and intimate partner violence (IPV). Methods: A novel social mapping methodology was adopted amongst a Yezidi population displaced by ISIS (ISIS: Islamic Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Although respondents were not specifically questioned about religion in relation to their experiences of forced displacement and GBV, 58 respondents raised the importance of religion, supporting claims made elsewhere about the significant role religion play in forced migrants" everyday lives (cf. Strang et al, 2020;Pertek, 2022b). Our analysis demonstrated that religion interacted with GBV in forced migration in multiple ways that, at times, generated increased "risks" or vulnerability to abuse but also served as a "protective" factor that was used as a coping and recovery mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Although respondents were not specifically questioned about religion in relation to their experiences of forced displacement and GBV, 58 respondents raised the importance of religion, supporting claims made elsewhere about the significant role religion play in forced migrants" everyday lives (cf. Strang et al, 2020;Pertek, 2022b). Our analysis demonstrated that religion interacted with GBV in forced migration in multiple ways that, at times, generated increased "risks" or vulnerability to abuse but also served as a "protective" factor that was used as a coping and recovery mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a strong therapeutic relationship is a suitable mechanism to help Yazidi survivors to speak of their trauma and has been attributed to positive intervention outcomes in non-conflict settings (Cloitre et al ., 2002 ; Keller et al ., 2010 ). However, applicability of this mechanism needs testing, for persistent persecution has amounted in a strong distrust of others, limiting engagement with psychosocial support services (Strang et al ., 2020 ). As expressed by one care provider: ‘Some of my patients do not believe we can help them at all.…”
Section: Discussionmentioning
confidence: 99%
“…Despite China has carried out a series of interventions (2), the HIV/AIDS epidemic has had a detrimental effect on people living with HIV/AIDS and their family members, including children and youths. Youths (aged [20][21][22][23][24][25][26][27][28][29][30] affected by parental HIV/AIDS, including youths who lost one or both of their parents to HIV/AIDS ("AIDS orphans") and youths who are living with HIV-infected parents ("Vulnerable children") (3,4). Previous research has focused on the effects of risk factors on the negative psychosocial adjustment (depressive symptoms, problem behaviors, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Mohanty et al ( 29 ) found that support from the targeted community could help nurses build personal and social connections and enhance trust in the community. Strang et al ( 30 ) found the support of families and communities was conducive to improving the trust of those becoming homeless by the conflict. Therefore, when youths affected by parental HIV/AIDS perceive more social support, they tend to have more social trust ( 31 ).…”
Section: Introductionmentioning
confidence: 99%